Geotechnical instrumentation in practice purpose, performance and interpretation (Thomas Telford, 1990)
A substantial and comprehensive source of information about the range of both practical and theoretical issues which the ground engineer needs to consider. The wide-ranging papers in this book draw together international experience in both research and practice.